Revenue and valuation of companies with digital platform business models - Pomykalski, Przemysław (Przychody i wycena firm stosujących model biznesu platformy cyfrowej, 2019)
Multisided, digital platforms attract considerable attention in business and academic circles. Seven out of the ten most valuable companies in the world derive much of their value from multisided platforms. The problem of defining and measuring value remains a major challenge in management literature. In this paper I analyze the relationship between the sales (revenue) and market capitalization of companies with digital platform business models. Data was used from a sample of 19 companies that used platform business models in 2017. To assess the correlation, Pearson correlation coefficient was applied. The results indicate that there was a significant positive relationship between revenue and market capitalization in 2017. This suggests that revenue may be used as the main variable in the valuation of companies using platform business models. The results point to future research problems that may be addressed using casebased methodology.
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 1; s. 11-18
Keywords: platforms; business model; valuation; platforma; model biznesu; wartość